If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3x = 7x + -4 Combine like terms: 5x + 3x = 8x 8x = 7x + -4 Reorder the terms: 8x = -4 + 7x Solving 8x = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 8x + -7x = -4 + 7x + -7x Combine like terms: 8x + -7x = 1x 1x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 1x = -4 + 0 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 6x^4-5x^3-4x^2=0 | | 5(x+7)=2(x+12)+2(x+1) | | -3Y-4X=0 | | 4cosx-7=0 | | 2[m-(3m+19)+16]=2(m+3) | | p+3=15-p | | 3.5(x+4)=1.4(16+x) | | -4(4-6d)=9(2d-2) | | 12+2.1x=1.3x | | 2.1x=1.2x-9 | | (y^2-9y+14)(2y+16)=0 | | -7v+5(v+3)=11 | | (X+8)(2x-4)=1008 | | -5(3y-9)-y=-3(y-5) | | 3x+7=-12 | | -7=z/8-2 | | 3*3x=2*5x+5*6 | | 3*3x=2.5x+5*6 | | 7-41x=2 | | z-(v+u)=-10 | | b=-8-(v-y) | | 8=575-5x | | 3x^5=15x^4 | | 4=575-5x | | 4=575-5 | | a=v+y-z | | x=v-a+8 | | 2=575-5x | | x/3-3=-4 | | c-v+x=b | | -1.1-5x=7.4 | | (6x+14)+(9x+5)= |